Pede Tanam 1.0, Sistem Informasi Debit Air Realtime Berbasis Internet of Things (IoT) - Bayu Dwi Apri Nugroho; Benyamin Nahak; Hertiyana Nur Annisa (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2023)
In an effort towards the industrial revolution 4.0, in modern irrigation management, conventional methods must be accompanied by technology. Then also the delivery of water discharge data to the Provincial Irrigation Commission secretariat is slow and not up to date, the Global Planting Plan (RTTG) and Detailed Planting Plan (RTTD) do not exist, an innovative Real-time Debit Logger (Pede Tanam 1.0) is needed. The way this tool works is through two sensors that are mounted on a cross section both in the primary irrigation canal and the data is processed by the microcontroller system to be sent via an internet connection quickly and accurately and the results are displayed in an application installed on a PC or mobile phone in the form of numerical data and graphics, as well area information can be streamed. Furthermore, information on the condition of the water debit can be printed automatically on the O-6 blank. The latest data transmission from sensors can be set every five minutes of updating. This new concept has been tested in the Manikin Irrigation Area, Kupang Regency, East Nusa Tenggara Province. The results of this study, that the water discharge meter in real time is running well, including updating data and also printing O-6 blanks directly from the Pede Tanam information system and from applications on smart phones. This will be very useful in the future, especially if implemented in areas that have islands, apart from efficiency problems, social conflicts can also be avoided.